1984
DOI: 10.1029/ja089ia01p00203
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent scatter observations of an artificially modified ionosphere

Abstract: The launch of NASA's HEAO‐C satellite by an Atlas/Centaur rocket on September 20, 1979, provided the first “experiment of opportunity” to test incoherent scatter radar techniques for the diagnostic study of a chemically‐induced modification of the ionosphere. The cause of the disturbance was the rocket's exhaust cloud of H2 and H2O molecules that cause a rapid recombination of the F region plasma at heights above 250 km. The launch from the Kennedy Space Center (28°N, 81°W) was monitored by the incoherent scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…Other Spacelab 2 burns over the Millstone Hill incoherent scatter radar showed similar enhanced backscatter above and below an ionospheric "hole" [Mendillo et al, 1987]. Similar radar signatures were recorded by the Millstone Hill incoherent scatter facility (42.6øN, 71.5øW) during the launch of an Atlas/Centaur rocket on September 20, 1979 [Wand and Mendillo, 1984]. The 440-MHz radar was 1780 km from the rocket exhaust trail when the observations were made.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Other Spacelab 2 burns over the Millstone Hill incoherent scatter radar showed similar enhanced backscatter above and below an ionospheric "hole" [Mendillo et al, 1987]. Similar radar signatures were recorded by the Millstone Hill incoherent scatter facility (42.6øN, 71.5øW) during the launch of an Atlas/Centaur rocket on September 20, 1979 [Wand and Mendillo, 1984]. The 440-MHz radar was 1780 km from the rocket exhaust trail when the observations were made.…”
mentioning
confidence: 54%
“…The theory developed here will apply to both space shuttle and Centaur rocket exhaust. The plasma in the exhaust plumes is taken to consist of molecular ions (predominantly H2 O+ with mass m m = 18 mp, where mp is proton mass), iono- Wand and Mendillo [1984]. The incoherent scatter is enhanced by factors of 1.2 above and below the location of the rocket plume.…”
Section: Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] The STIM background neutral atmosphere, along with the time-evolution of a bulge of water density resulting [Moore et al, 2006]: a region of photochemical equilibrium, wherein ion production/loss rates are balanced (tan), a diffusive regime dominated by transport processes (orange), and a heavy ion regime dominated by hydrocarbon and/or metallic ions (light blue). (b) Terrestrial profiles demonstrating the formation of an ''ionospheric hole'' in response to exhaust gases from the launch of NASA's HEAO-C satellite [Wand and Mendillo, 1984]. from a point-source release at Saturn, is shown in the left column of Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Mendillo et al (1975) present beacon-satellite observations of TEC in the vicinity of the trajectory of the Skylab launch while Wand and Mendillo (1984) report Millstone Hill radar observations of the ionospheric e ects of the launch of HEAO-C. Neither of these daytime studies observed any persistent oscillations of the ionosphere following the creation of large-scale ionospheric holes by the launch-vehicle exhaust products at F-region heights.…”
Section: Persistent E Ects Of Arti®cial Ionospheric Perturbationmentioning
confidence: 99%